2013
DOI: 10.1177/0022022113493139
|View full text |Cite
|
Sign up to set email alerts
|

Joint Drumming in Brazilian and German Preschool Children

Abstract: As a core feature of musical rituals around the world, humans synchronize their movements to the pulse of a shared acoustic pattern-a behavior called rhythmic entrainment. The purpose of the present study was (a) to examine the development of rhythmic entrainment with a focus on the role of experience and (b) to follow one line of evidence concerning its adaptive function. We hypothesized (a) that children learn how to synchronize movements to sound during social interactions, where they experience this behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 74 publications
4
48
1
1
Order By: Relevance
“…The need to investigate potential moderators has been emphasized by recent failed replications (Kirschner & Ilari, 2013; Schachner & Mehr, 2015). In this meta-analysis, we examined the following potential moderators.…”
Section: Consequences Of Msis and Potential Moderatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to investigate potential moderators has been emphasized by recent failed replications (Kirschner & Ilari, 2013; Schachner & Mehr, 2015). In this meta-analysis, we examined the following potential moderators.…”
Section: Consequences Of Msis and Potential Moderatorsmentioning
confidence: 99%
“…However, no quantitative review to date has integrated the scattered experiments on the social consequences of interpersonal synchrony. Furthermore, little is known about the variables that moderate interpersonal synchrony’s potential effects on social outcomes – a fact that appears to be particularly relevant in light of failed replications (Kirschner & Ilari, 2013; Schachner & Mehr, 2015). …”
mentioning
confidence: 99%
“…That is, at least two elements that enable rhythmic entrainment (i.e., perception and production of body movements to perceived rhythmic and metric structures) are already present in early life (Phillips-Silver, Aktipis, & Bryant, 2010). The other two elements, namely, the integration of perception and production and the adjustment of body movements to perceived beats and metric structures (see Phillips-Silver et al, 2010), take some time to develop (for a discussion see Kirschner & Ilari, 2014). Furthermore, there are substantial individual differences in children's rhythmic entrainment abilities, as the latter are influenced by formal music education (Drake, Jones, & Baruch, 2000), culture (Kirschner & Ilari, 2014), and social context (Eerola et al 2006;Kirschner & Tomasello, 2009).…”
Section: Three Building Blocks Of Social Cognition In Early Childhoodmentioning
confidence: 99%
“…Some studies have also demonstrated that coordinated movements strengthen several pro-social behaviors. For example, episodes of coordinated activity enhance helpfulness in infants (Cirelli et al, 2014a,b, 2016) and children (Kirschner and Tomasello, 2010; Kirschner and Ilari, 2014; Endedijk et al, 2015). Similar results have been reported for adults.…”
Section: Introductionmentioning
confidence: 99%